The effects of plasma source on adiabatic electron acceleration at dipolarization fronts - Chepuri, S. N. F.; Jaynes, A. N.; Joseph, J.; Turner, D. L.; Gabrielse, C.; Cohen, I. J.; Baker, D. N.; Mauk, B. H.; Leonard, T.; Fennell, J. F. (Frontiers in Astronomy and Space Sciences, 2025)
Particle acceleration is a commonly observed phenomenon at dipolarization fronts. Many studies have attempted to determine the acceleration mechanism, with betatron acceleration being a major candidate. In previous work, we attempted to match the observed change in electron energy to the change predicted by betatron acceleration, but found that although this worked in some cases, overall betatron acceleration alone could not describe the observed energy spectrum changes. In this work, we attempted to study whether ion acceleration showed similar behavior and whether a quasi-adiabatic correction would be more accurate. On average the betatron acceleration equation overestimated the observed acceleration and the quasi-adiabatic correction did not account for the difference, although there are limitations to this study due to data fidelity. We then turned to study whether our assumptions about the source population having the same phase space density as the cold pre-existing background population in the plasma sheet are valid. We indirectly studied this by comparing the relative abundances of O+ and He++ as proxies for ionospheric and solar wind populations respectively. We found the betatron acceleration equation method performs slightly better when there is a stronger ionospheric component. This suggests that when more plasma containing O+ is present in the dipolarization front, it indicates that the source population is more local and therefore this method of using betatron acceleration is more valid.